Hubungan Tingkat Kebugaran dengan Tingkat Konsentrasi Wasit PSSI Kabupaten Musi Rawas - Rifa'i, Nova; Erwandi, Rudi (Gelanggang Olahraga: Jurnal Pendidikan Jasmani dan Olahraga (JPJO), 2025)
This research aims to determine the relationship between fitness level and concentration level of PSSI referees in Musi Rawas Regency. The research method used by researchers is correlation. The population of all PSSI referees in Musi Rawas Regency is 17 people and the sampling technique is porpusive sampling, 14 people. The data collection technique uses the FIFA.2016 test. Multistag Fitness Test and Grid Concentration Test. Data analysis techniques for normality testing, linearity testing, and hypothesis testing use the SPSS version 22 program. Based on the results of data analysis, researchers concluded that there is a relationship between fitness level and concentration level of PSSI referees in Musi Rawas Regency, with a significant value of 0.05 and a correlation coefficient of 0.573, which means it has moderate closeness, so it can be calculated that the coefficient of determination is 32.9%, meaning that the contribution of the physical fitness variable to concentration is 32.9%. Keywords: Concentration and Referee, Fitness